Religiosity in Wedhatama by KGPAA Mangkunagara IV: An Education Model A La Javanese Culture - Ismawati, Esti (International Journal of Active Learning, 2016)
This research purpose is to describe religious values in Wedhatama by and its relevance to todays life. The method used is descriptive inferential, by describing religious values in Wedhatama which is in form of Pangkur, Sinom, Pucung,andGambuh, and after that, summarizing it. The analysis results in conclusion that Wedhatama by Mangkunagara IV contains high religious values, which is manifested in a belief that human beings depend on God and God is a source of salvation, so human beings should be close to or surrender deeply to God. Religious person is imagined in Wedhatama as prime being, who loves solitude, tawadu, always be humble (he is not angry when someone calls him stupid), has less desire, puts his trust in God and sincere, knows the end, learns the essence of desolation, responses well to his wishes, sensitive, kind hearted, and loves to meditate until he finds some divine revelations, and imitates behaviors like in fiqh. This is education model a la Javanese culture, which is still relevance to be done by all people in this world.How to CiteIsmawati, E. (2016). Religiosity in Wedhatama by KGPAA Mangkunagara IV: An Education Model A La Javanese Culture. International Journal of Active Learning, 1(1).